Impact of the coronavirus disease 2019 pandemic on critical care healthcare workers' depression, anxiety, and stress levels. Issue 2 (March 2021) - Hammond, Naomi E.; Crowe, Liz; Abbenbroek, Brett; Elliott, Rosalind; Tian, David H.; Donaldson, Lachlan H.; Fitzgerald, Emily; Flower, Oliver; Grattan, Sarah; Harris, Roger; Sayers, Louise; Delaney, Anthony
Abstract: Aim: The aim of the study was to determine levels of depression, anxiety, and stress symptoms and factors associated with psychological burden amongst critical care healthcare workers in the early stages of the coronavirus disease 2019 pandemic. Methods: An anonymous Web-based survey distributed in April 2020. All healthcare workers employed in a critical care setting were eligible to participate. Invitations to the survey were distributed through Australian and New Zealand critical care societies and social media platforms. The primary outcome was the proportion of healthcare workers who reported moderate to extremely severe scores on the Depression, Anxiety, and Stress Scale-21 (DASS-21). Results: Of the 3770 complete responses, 3039 (80.6%) were from Australia. A total of 2871 respondents (76.2%) were women; the median age was 41 years. Nurses made up 2269 (60.2%) of respondents, with most (2029 [53.8%]) working in intensive care units. Overall, 813 (21.6%) respondents reported moderate to extremely severe depression, 1078 (28.6%) reported moderate to extremely severe anxiety, and 1057 (28.0%) reported moderate to extremely severe stress scores. Mean ± standard deviation values of DASS-21 depression, anxiety, and stress scores amongst woman vs men was as follows: 8.0 ± 8.2 vs 7.1 ± 8.2 (p = 0.003), 7.2 ± 7.5 vs 5.0 ± 6.7 (p < 0.001), and 14.4 ± 9.6 vs 12.5 ± 9.4 (p < 0.001), respectively. After adjusting for significant confounders, clinical concerns associated with higher DASS-21 scores included not being clinically prepared (β = 4.2, p < 0.001), an inadequate workforce (β = 2.4, p = 0.001), having to triage patients owing to lack of beds and/or equipment (β = 2.6, p = 0.001), virus transmission to friends and family (β = 2.1, p = 0.009), contracting coronavirus disease 2019 (β = 2.8, p = 0.011), being responsible for other staff members (β = 3.1, p < 0.001), and being asked to work in an area that was not in the respondents' expertise (β = 5.7, p < 0.001). Conclusion: In this survey of critical care healthcare workers, between 22 and 29% of respondents reported moderate to extremely severe depression, anxiety, and stress symptoms, with women reporting higher scores than men. Although female gender appears to play a role, modifiable factors also contribute to psychological burden and should be studied further.